Enabled to eat more plant proteins? Capabilities, opportunities, and motivations related to increasing pulse and pulse-based product consumption across consumer groups - Kuosmanen, Sini; Korhonen, Kirsi; Pajari, Anne-Maria; Konttinen, Hanna (Elsevier, 2025)
Replacing even part of dietary red meat with plant proteins, such as pulses, is associated with better environmental and human health. Despite this, meat consumption is still popular while plant proteins are underconsumed in the Western world, especially among certain consumer groups. In this paper, our objective was to examine to what extent 15 different enablers would advance the consumption of pulses and pulse-based products (PBPs) across different genders, age groups, education levels, perceived financial situations, and red meat-eating frequencies. A survey was conducted among Finnish adults aged 18–75 years (n = 1000). The main analysis technique was multivariable linear regression. The Capability, Opportunity, Motivation, Behavior (COMsingle bondB) model was applied in discussing the results. The most important enablers for increasing pulse and PBP consumption were better taste, lower price, and having recipes and ideas for use provided, which represent motivation, opportunity, and capability in the COM-B model. In general, women, the young, and respondents with less frequent red meat consumption perceived the enablers could increase their pulse and PBP consumption more than men, older respondents, and those with frequent red meat consumption. Additionally, the effects of age, financial situation, and red meat consumption frequency on the perceived importance of some of the enablers varied between women and men. Taken together, consumer groups differed in the importance of all three COM-B elements. These results can be used to promote plant-based eating among different consumer groups and allow the design of increasingly targeted interventions.
Keywords: alternative protein; plant-based diet; legumes; socioeconomic differences; gender; COM-B